233k views
5 votes
Solve for x: 4 over x plus 4 over quantity x squared minus 9 equals 3 over quantity x minus 3. (2 points) Select one: a. x = -4 and x = -9 b. x = 4 and x = -9 c. x = -4 and x = 9 d. x = 4 and x = 9

1 Answer

2 votes

Answer:

c. x = -4 or x = 9

Explanation:


(4)/(x)+(4)/(x^2-9)=(3)/(x-3)

Domain:


x\\eq0\ \wedge\ x^2-9\\eq0\ \wedge\ x-3\\eq0\\\\x\\eq0\ \wedge\ x\\eq\pm3

solution:


(4)/(x)+(4)/(x^2-3^2)=(3)/(x-3)

use (a - b)(a + b) = a² - b²


(4)/(x)+(4)/((x-3)(x+3))=(3)/(x-3)

multiply both sides by (x - 3) ≠ 0


(4(x-3))/(x)+(4(x-3))/((x-3)(x+3))=(3(x-3))/(x-3)

cancel (x - 3)


(4(x-3))/(x)+(4)/(x+3)=3

subtract
(4(x-3))/(x) from both sides


(4)/(x+3)=3-(4(x-3))/(x)\\\\(4)/(x+3)=(3x)/(x)-((4)(x)+(4)(-3))/(x)\\\\(4)/(x+3)=(3x-\bigg(4x-12\bigg))/(x)\\\\(4)/(x+3)=(3x-4x-(-12))/(x)\\\\(4)/(x+3)=(-x+12)/(x)

cross multiply


(4)(x)=(x+3)(-x+12)

use FOIL


4x=(x)(-x)+(x)(12)+(3)(-x)+(3)(12)\\\\4x=-x^2+12x-3x+36

subtract 4x from both sides


0=-x^2+12x-3x+36-4x

combine like terms


0=-x^2+(12x-3x-4x)+36\\\\0=-x^2+5x+36

change the signs


x^2-5x-36=0\\\\x^2-9x+4x-36=0\\\\x(x-9)+4(x-9)=0\\\\(x-9)(x+4)=0

The product is 0 if one of the factors is 0. Therefore:


x-9=0\ \vee\ x+4=0


x-9=0 add 9 to both sides


x=9\in D


x+4=0 subtract 4 from both sides


x=-4\in D

User Patrick White
by
6.0k points